Pharmacogenomics and Adverse Drug Reactions: Carbamazepine Induced Steven Johnsons Syndrome - Dadwai, Akhila; Navar, Karthika; Bagilipeddola, Manasa; Rajannagari, Rajareddy; Nittu, Satyavardhan Rao (Journal of Pharmacy Practice and Community Medicine)
Background: Carbamazepine, an anticonvulsant and a mood-stabilizing drug is the main cause of the Stevens- Johnson Syndrome (SJS) and its related disease, toxic epidermal necrolysis (TEN), in Southeast. Asian countries. Carbamazepine-induced SJS-TEN is strongly associated with the HLA-B*1502 allele. Case report: An eight-yearold female was admitted to the pediatric ward with chief complaints of macular rash all over the body, itching and giddiness for a week, on the evaluation of her history reveals that she is an epileptic on medication Carbamazepine 100 mg once-daily dose. On the 10th day of CBZ therapy, the patient developed macular rashes all over the body and CBZ was discontinued. Hence, the final diagnosis was made as Carbamazepine induced Steven-Johnson syndrome.
Keywords: Carbamazepine; Steven-Johnson syndrome; Toxic epidermal necrolysis; HLA-B*; Adverse reactions; Pharmacogenomics.